Are skeletal muscle FNDC5 gene expression and irisin release regulated by exercise and related to health? - Pekkala, Satu; Wiklund, Petri K.; Hulmi, Juha J.; Ahtiainen, Juha P.; Horttanainen, Mia; Pöllänen, Eija; Mäkelä, Kari A.; Kainulainen, Heikki; Häkkinen, Keijo; Nyman, Kai; Alén, Markku; Herzig, Karl‐Heinz; et al. (The Journal of physiology, 2013)
Key points • Contradictory findings have been reported concerning the function of irisin and its precursor gene, skeletal muscle FNDC5, in energy homeostasis and metabolic health, and the associated regulatory role of exercise and PGC‐1α. • We analysed the effects of different short‐ and long‐term exercise regimens on muscle FNDC5 and PGC‐1α, and serum irisin, and studied the associations of irisin and FNDC5 with health parameters. • FNDC5 and serum irisin did not change after acute aerobic, long‐term endurance training or endurance training combined with resistance exercise (RE) training, or associate with metabolic disturbances. A single RE bout increased FNDC5 mRNA in young, but not older men (27 vs. 62 years). Changes in PGC‐1α or serum irisin were not consistently accompanied by changes in FNDC5. • Our data suggest that the effects of exercise on FNDC5 and irisin are not consistent, and that their role in health is questionable. Moreover, the regulatory mechanisms should be studied further. Recently, contradictory findings have been reported concerning the function of irisin and its precursor gene, skeletal muscle FNDC5, in energy homeostasis, and the associated regulatory role of exercise and PGC‐1α. We therefore evaluated whether muscle FNDC5 mRNA and serum irisin are exercise responsive and whether PGC‐1α expression is associated with FNDC5 expression. The male subjects in the study performed single exercises: (1) 1 h low‐intensity aerobic exercise (AE) (middle‐aged, n= 17), (2) a heavy‐intensity resistance exercise (RE) bout (young n= 10, older n= 11) (27 vs. 62 years), (3) long‐term 21 weeks endurance exercise (EE) training alone (twice a week, middle‐aged, n= 9), or (4) combined EE and RE training (both twice a week, middle‐aged, n= 9). Skeletal muscle mRNA expression was analysed by quantitative PCR and serum irisin by ELISA. No significant changes were observed in skeletal muscle PGC‐1α, FNDC5 and serum irisin after AE, EE training or combined EE + RE training. However, a single RE bout increased PGC‐1α by 4‐fold in young and by 2‐fold in older men, while FNDC5 mRNA only increased in young men post‐RE, by 1.4‐fold. Changes in PGC‐1α or serum irisin were not consistently accompanied by changes in FNDC5. In conclusion, for the most part, neither longer‐term nor single exercise markedly increases skeletal muscle FNDC5 expression or serum irisin. Therefore their changes in response to exercise are probably random and not consistent excluding the confirmation of any definitive link between exercise and FNDC5 expression and irisin release in humans. Moreover, irisin and FNDC5 were not associated with glucose tolerance and being overweight, or with metabolic disturbances, respectively. Finally, factor(s) other than PGC‐1α and transcription may regulate FNDC5 expression.